River Rose and the magical Christmas - Clarkson, Kelly, 1982- (Harper, an imprint of HarperCollinsPublishers, 2017)
On Christmas Eve, River Rose accidentally falls asleep while trying to wait up for Santa, but she awakens to take a magical trip to the North Pole with her dog, Joplin.